Impact of trimethylaminuria on daily psychosocial functioning. Issue 1 (6th October 2020) - Roddy, Daniel; McCarthy, Philomena; Nerney, Darragh; Mulligan‐Rabbitt, Jennifer; Smith, Edwin; Treacy, Eileen P.
Abstract: Background: Trimethylaminuria (TMAU) (OMIM #602079) is a rare inherited metabolic condition. TMAU is associated with decreased hepatic trimethylamine N‐oxidation, which leads to an excess of the volatile trimethylamine (TMA) instead of substrate conversion to trimethylamine N‐oxide (TMAO). TMA is a tertiary amine derived from the enterobacterial metabolism of precursors such as choline and phosphatidylcholine present in the diet, and is also a bacterial metabolite of TMAO, a normal constituent of saltwater fish. When the involved enzyme flavin mono‐oxygenase 3 is deficient, TMA builds up and is released in the person's sweat, urine, and breath, giving off a strong body odor. We have recently reported the biochemical and genetic characteristics of 13 Irish adult patients with TMAU attending the main Irish Reference Center. Research on the behavioral and psychosocial aspects of this condition is limited. This study explores the patients' perspectives of living with TMAU in Ireland. Methods: A qualitative descriptive phenomenological approach was used. Six adults participated in this study. Data were gathered through semi‐structured interviews, which were transcribed and analyzed. Results: The results suggest that the participants experienced a negative journey to diagnosis. Fear, anxiety, paranoia, and dysfunctional thinking are a constant struggle. Participants reported using avoidant coping mechanisms and strategic planning to navigate daily life. Conclusion: It is considered that the results from this study will inform future interventions with this unique patient cohort.